An association between liraglutide treatment and reduction in excessive daytime sleepiness in obese subjects with type 2 diabetes. Issue 1 (December 2015) - Gomez-Peralta, Fernando; Abreu, Cristina; Castro, Jose; Alcarria, Elvira; Cruz-Bravo, Margarita; Garcia-Llorente, Maria; Albornos, Cristina; Moreno, Concepción; Cepeda, María; Almodóvar, Francisca
Abstract Background The main purpose of the present study is to evaluate whether treatment with long-acting human glucagon-like peptide-1 liraglutide was associated with an improvement of excessive daytime sleepiness (EDS) in obese subjects with type-2 diabetes. Methods This single-centre retrospective study included 158 obese (body mass index [BMI] ≥ 30 kg/m2 ) adult subjects with type-2 diabetes who were initiated with liraglutide treatment at least 3 months before study inclusion. Data of the Epworth Sleepiness Scale (ESS), anthropometric parameters, glucose-control and metabolic parameters were collected at liraglutide initiation (baseline) and at months 1 and 3 after liraglutide initiation. Results Significant reductions in ESS score were achieved at months 1 (−1.3 ± 2.8, p  < 0.001) and 3 (−1.5 ± 3.0, p  < 0.001) after liraglutide introduction. After 3 months of treatment with liraglutide, significant changes in body weight (p  < 0.001), BMI (p  < 0.001), waist (p  < 0.001) and neck circumferences (p  < 0.005), HbA1c (p  < 0.001), mean blood glucose (p  < 0.001), fasting plasma glucose (p  < 0.001), triglycerides (p  < 0.01) and total cholesterol (p  < 0.001) were achieved. Conclusions After 3 months of treatment with liraglutide a significant reduction in EDS was observed in obese subjects with type-2 diabetes. Besides this, significant changes in body weight and metabolic parameters of diabetes control were also accomplished. Further investigation is required to determine whether liraglutide could improve other abnormal sleep patterns and obstructive sleep apnoea.